Gerakan Dakwah Islam Liberal di Indonesia: Analisis Kritis dalam Lanskap Kontemporer - Anggraini, Reti Dwi; Pradesa, Dedy (STID Al-Hadid, 2025)
THE LIBERAL ISLAMIC DA'WAH MOVEMENT IN INDONESIA: A CRITICAL ANALYSIS IN THE CONTEMPORARY LANDSCAPE. The emergence of the liberal Islamic missionary movement in Indonesia, led by the Liberal Islam Network (JIL) in the early 2000s, sparked both support and opposition. JIL, as an intellectual missionary movement in contemporary development, is no longer active organizationally. However, liberal Islamic da'wah has not simply ceased to exist, as it continues to manifest itself in various forms of movement, both structured and sporadic. It is still being promoted through new, more contemporary channels. This study aims to further describe how the liberal Islamic da'wah movement in Indonesia operates within the contemporary landscape, while also providing a critical analysis of liberal Islamic da'wah in Indonesia. The methodology used is qualitative literature review. The study results indicate that liberal Islam in Indonesia in the contemporary era has evolved alongside changes in the da'wah landscape it faces. These changes include aspects of subject matter, methods and media, as well as the packaging of the content or message of liberal Islamic preaching, even though the main ideas being preached remain the same as before. In terms of divine preaching, changes in the operational methods of preaching are universal as a response to changing circumstances. The challenges of liberal Islamic da'wah lie in the core ideas of its messages, which pertain to secularism, pluralism, liberalism, gender equality, and the safety of non-Muslims. These messages cannot be categorized as a continuation of divine da'wah. On the contrary, in some aspects, they compromise the principles of divine da'wah